Efficacy and Safety of Panax notoginseng Saponin Therapy for Acute Intracerebral Hemorrhage, Meta-Analysis, and Mini Review of Potential Mechanisms of Action - Xu, Dongying; Huang, Ping; Yu, Zhaosheng; Xing, Daniel H.; Ouyang, Shuai; Xing, Guoqiang (Frontiers in Neurology, 2015)
Intracranial/intracerebral hemorrhage (ICH) is a leading cause of death and disability in people with traumatic brain injury (TBI) and stroke. No proven drug is available for ICH. Panax notoginseng (total saponin extraction, PNS) is one of the most valuable herb medicines for stroke and cerebralvascular disorders in China. We searched for randomized controlled clinical trials (RCTs) involving PNS injection to treat cerebral hemorrhage for meta-analysis from various databases including the Chinese Stroke Trials Register, the trials register of the Cochrane Complementary Medicine Field, the Cochrane Central Register of Controlled Trials, MEDLINE, Chinese BioMedical disc, and China Doctorate/Master Dissertations Databases. The quality of the eligible trials was assessed by Jadad’s scale. Twenty (20) of the 24 identified randomized controlled trials matched the inclusive criteria including 984 ICH patients with PNS injection and 907 ICH patients with current treatment (CT). Compared to the CT groups, PNS-treated patients showed better outcomes in the effectiveness rate (ER), neurological deficit score (NDS), intracranial hematoma volume (IHV), intracerebral edema volume (IEV), Barthel Index (BI), the number of patients died (NDP) and incidence of adverse events. Conclusion: PNS injection is superior to CT for acute ICH. A review of the literature shows that PNS may exert multiple protective mechanisms against ICH-induced brain damage including hemostasis, anti-coagulation, anti-thromboembolism, cerebral vasodilation, invigorated blood dynamics, anti-inflammation, antioxidation and anti-hyperglycemic effects. As PNS has a long clinical track record in Asia, it could potentially become a therapy option to treat ICH in the US and Europe. Further clinical trials with better experimental design could determine the long-term effects of PNS treatment for TBI and stroke.